GIS SPATIAL MODEL FOR NATURAL RESOURCE MANAGEMENT (NRM) FOR INDIGENOUS COMMUNITIES IN INDONESIA AND MALAYSIA - Pitalis Mawardi Baging; Ihsan Nurhakim (GeoEco, 2026)
Natural resource management (NRM) in indigenous communities plays a crucial role in sustaining environmental resources and improving rural livelihoods. However, indigenous knowledge related to NRM is often poorly documented and rarely integrated into systematic environmental management planning, creating gaps in sustainable resource governance. This study aims to analyse and model the implementation planning of natural resource management based on indigenous knowledge levels and natural resource deterioration factors in selected indigenous villages in Indonesia and Malaysia. Data were collected from 200 respondents across four indigenous villages: Saham, Pahuman (Sengah Temila), and Mandor in Landak Regency, West Kalimantan (Indonesia), and Serendah in Hulu Selangor (Malaysia). Hierarchical Agglomerative Cluster Analysis (HACA) was used to classify nine questionnaire variables (SC1–SC9) related to knowledge and environmental deterioration factors. The clustering results were further integrated with Geographic Information System (GIS) spatial modelling using the Inverse Distance Weighting (IDW) interpolation method to analyse spatial distribution patterns of the identified models. The analysis produced five natural resource management implementation models: Model A (innovation of existing management systems), Model B (development of management systems), Model C (application of new technologies such as GIS), Model D (guidance from responsible environmental authorities), and Model E (government commitment). Spatial analysis revealed strong community support for these models, with agreement levels reaching approximately 95% in Serendah Village and generally positive responses across villages in Landak Regency. These findings highlight the importance of integrating indigenous knowledge, technological approaches, and institutional support to strengthen sustainable natural resource management in indigenous communities.